EXPRESSION OF ANGIOPOETIN ON THE KIDNEY TRANSPLANT WAITING LIST: A SINGLE-CENTER STUDY - Süleyman Rüştü Oğuz; Ayşe Sinangil; Demet Kıvanç İzgi; Soykan Barlas; Hayriye Şentürk Çiftçi; Kıymet Güzin Şen; Tevfik Ecder; Barış Akın (Sabiad)
Objective: Angiopoietin-2 (Ang-2) is a growth factor belonging to the angiopoietin (Ang)/Tie signaling pathway. Plasma levels of especially Ang- 2, are thought to be significantly increased in patients with acute kidney injury (AKI), independent of inflammation. Ang-2 is also important in dialysis and transplantation, as it plays an important role in the disruption of endothelial homeostasis. Our study aimed to investigate the relationship between anti-HLA antibody loads and Ang levels in patients with endstage renal disease (ESRD) who are on the organ transplant waiting list.Material and Method: 80 ESRD patients who were on the waiting list between 2018 and 2020 and whose panel reactive antibody (PRA) screening and identification test were studied participated in our study. First, the PRA screening test was performed on the patients, and the class I-II identification tests were studied on the patients who were positive for PRA. The Ang-2 level was evaluated by the ELISA method. The relationship between Ang-2 levels and PRA percentages in PRA positive and negative patients was evaluated.Results: A positive correlation was found between anti-HLA antibody and Ang-2 levels in patients with ESRD (class I, p=0.024; class II, p=0.032), and a statistically significant increase in Ang-2 level was found in patients with PRA ≥50% positive (class I, p=0.038) This finding suggests that Ang-2 may have an important role in the progression of chronic renal failure and may be effective in predicting graft survival after transplantation. Conclusions: Further studies will be required to fully elucidate the effect of Ang-2 on renal progression.